Relación de horas de sueño, presión arterial y glicemia en ayunas en estudiantes de medicina - Meléndez Benites, César Ricardo (2023)
To evaluate if there is a relationship between the duration of sleep hours with blood pressure and fasting glycemia in medical students. Materials and methods: An analytical and cross-sectional correlational study with random sampling was carried out using a data collection form. The average of three blood pressure (BP) readings and fasting glycemia were recorded. One-dimensional and two-dimensional frequency distribution tables with their absolute and relative values, and the chi-square test (p<0.05) were used. Results: Of the 92 medical students included in the sample, 53.3% were male and the mean age was 23.7 ± 2.08 SD years. 69.6% of the participants affirmed having had sleep restriction, of which 1.6% presented normal-high systolic BP (X²=1.9 ; P=0.1655), 4,7% they had normal-high diastolic BP (X²=0.1 ; P=0.9609), 6,2% had arterial hypertension and 34.4% (X²=3.8; P=0.049) had prediabetes. Conclusions: If there is an inverse relationship between the hours of sleep of medical students with fasting glucose levels. No statistically significant association was found between the hours of sleep with the elevation of systolic BP and diastolic BP.